Phosphate and Oxysterols May Mediate an Inverse Relationship Between Atherosclerosis and Cancer - Ronald B. Brown (European Medical Journal Oncology, 2020)
The peer-reviewed literature has reported an inverse relationship between atherosclerosis and cancer for almost 100 years, but no causative mechanism has been established to explain this puzzling relationship. More recent research has reported an association between tumourigenesis and phosphate toxicity from dysregulated phosphate metabolism, and an association has also been reported between atherosclerosis and cholesterol oxidation products or oxysterols. The present review article synthesises these research findings and proposes that an inverse relationship between the associated risk of cancer and atherosclerosis may be mediated by tumourigenic and atherogenic dietary patterns containing inverse proportions of dietary phosphate and oxysterols. Low-fat animal-based foods generally have reduced cholesterol and oxysterol levels and relatively higher protein and phosphate levels, and dietary patterns containing these foods are associated with reduced atherosclerosis risk and increased cancer risk. By comparison, full-fat animal-based foods are higher in cholesterol and oxysterols and relatively lower in protein and phosphate, and dietary patterns containing these foods are associated with increased atherosclerosis risk and reduced cancer risk. Fruits, vegetables, and plant-based fats generally have lower phosphate levels and no cholesterol, and dietary patterns associated with increased amounts of these foods, such as the Mediterranean diet, reduce risk for both cancer and cardiovascular disease.